2018
DOI: 10.2196/10726
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Underlying Factors Associated With Patients’ Attitudes Toward Antidepressants: Qualitative and Quantitative Analysis of Patient Drug Reviews

Abstract: BackgroundNonadherence to antidepressants is a major obstacle to deriving antidepressants’ therapeutic benefits, resulting in significant burdens on the individuals and the health care system. Several studies have shown that nonadherence is weakly associated with personal and clinical variables but strongly associated with patients’ beliefs and attitudes toward medications. Patients’ drug review posts in online health care communities might provide a significant insight into patients’ attitude toward antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Building on our previous experiences and lessons learned from the content analysis of patients’ narratives, we propose a systematic framework to address the subjective nature of patients’ narratives [11,18-20]. This framework integrates text mining methods, the framework method, and deductive-inductive approach for content analysis and is composed of 4 main phases: (1) data collection, (2) data preparation, (3) content analysis, and (4) interpretation of the results.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Building on our previous experiences and lessons learned from the content analysis of patients’ narratives, we propose a systematic framework to address the subjective nature of patients’ narratives [11,18-20]. This framework integrates text mining methods, the framework method, and deductive-inductive approach for content analysis and is composed of 4 main phases: (1) data collection, (2) data preparation, (3) content analysis, and (4) interpretation of the results.…”
Section: Methodsmentioning
confidence: 99%
“…In the following sections, we demonstrate the implementation of each step of this systematic framework using 2 studies: (1) a case study that identified factors affecting patients attitudes toward antidepressants; we use the short title attitude to antidepressants to refer to this case study [11] and (2) a case study that analyzed the strategies and solutions of patients with diabetes facing financial difficulties to access medications and supplies; we use the short title access to diabetes medications to refer to this case study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations